Relationship Between Helicobacter pylori Infection Fasting Plasma Glucose Concentration Bordering - Meroj A. Jasem; Ali H. Alwan; Fatin M. Mahdi (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2010)
Helicobacter pylori gastritis results in an increased secretion of basal and meal-stimulated gastrin, which is also a physiologic amplifier of insulin release. Aim of the study: To detect the relationship between H. pylori infection and fasting blood glucose concentration. The study was performed on 209 patients (112 females and 97 males) and 22 control subjects were referring to Immunology Dep. in Central Public Health Laboratories for the period from August 2007 to June 2008, where H.pylori was diagnosed serologically. Fasting serum glucose concentrations had been measured by the glucose oxidase procedure.